PENGEMBANGAN MEDIA SLIDE INTERAKTIF BERBASIS POWERPOINT PADA SUBMATERI INVERTEBRATA DI SMA NEGERI 1 TEKARANG - Indriyana, Indriyana; Candramila, Wolly; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to produce a media in the form of powerpoint-based interactive slides that was feasible to be used in the teaching-learning process and to know the students' response related to the submaterial of Invertebrate in SMA Negeri 1 Tekarang of Sambas Regency. School determination was based on the availability of the tools and infrastucture potential but still found a problem that is the used powerpoint as the media in teaching learning with teacher centered  approach and narrative explanation which made the studens'  became passive and their learning result relatively low. The research and development method was implemented within 6 steps, including 1) potential and problem, 2) data collection, 3) product design, 4) expert validation, 5) product revision, and 6) product testing. s. The power point-based interactive slides were categorized valid which scored 3.67 by material experts and 3.77 by media experts. Moreover, the students were giving a positive response with the percentage of 81.41% which indicated that the powerpoint-based interactive slides were proper to be used as an instructional media in the Sub Material of Invertebrate for first-grade high school. Keywords: Powerpoint-Based Interactive Slides, Research and Development,Student?s Response, Sub Material of Invertebrate